(untitled) (International Journal of Engineering and Computer Science, 2014)
Image fusion is a process by which complimentary details from multiple input images are integrated into a single image, where the output fused image provide more information and more suitable for the purpose of human visual perception. Several situations in image processing require high spatial and high spectral resolution in a single image, to achieve this one solution is image fusion. There are several image fusion techniques are present those can improve the quality of image and provide more extended depth detail. This paper presents classification of some of the image fusion techniques such as Spatial Domain Fusion(Averaging method, Brovey Method, Principal Component Analysis, IHS) and transform domain fusion(multiresolution, Laplacian pyramid, Curvlet transform based, Discrete Wavelet transform ). Comparison of all the techniques concludes the better approach for its future research.